UPN “Veteran” East Java’s Strategy in Creating Students with a National Defense Character - Pasya Ramadhani Delina Swartama; Sri Wibawani (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to analyse and describe the strategy of UPN “Veteran” East Java in realising the appearance of students with national defence character as part of the implementation of the university's vision of